THE INFLUENCE OF REALISTIC MATHEMATICS EDUCATION ON YEAR 8 STUDENTS' SPATIAL ABILITY OF CUBOIDS AND CUBES - Nuryami Nuryami; Tuhfatul Janan; Nur Hasanah (KALAMATIKA Jurnal Pendidikan Matematika, 2022)
This study aims to determine the effect of RME on the spatial abilities of Year 8 students concerning cuboids and cubes. Geometry problems often experienced by junior high school students, such as difficulty knowing the difference between cuboids and cubes, difficulties showing elements of cuboids and cubes, and difficulty imagining cuboids and cubes in the case of rotation. The teacher should not underestimate it because it will impact the next level of learning. Besides, spatial abilities are closely related to other mathematical concepts. One alternative is using RME. This research employed the quasi-experimental method, and samples were selected using purposive sampling techniques. The two classes were selected as samples in this study: the experimental and the control classes. Before conducting the main analysis test, the pre-test score students were tested with the t-test. The initial conclusion was that there was no difference in the spatial ability of the experimental class and the control class. The main analytic test in the post-test was done using U-test. The post-test results show that the average score of the experimental class is higher than the control class; RME positively influences students' spatial abilities.